There Are Thin Minimizers of the L1TV Functional - Benjamin Van Dyke; Kevin R. Vixie (Abstract and Applied Analysis)
We show the surprising results that while the local reach of the boundary of an 𝐿1𝑇𝑉 minimizer is bounded below by 1/𝜆, the global reach can be smaller. We do this by demonstrating several example minimizing sets not equal to the union of the 1/𝜆-balls they contain.